(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Fistula in ano has been a troublesome pathology to both patients and surgeons throughout surgical history. Several techniques have been described for the management of fistula-in-ano but all carry their own risks of recurrence and incontinence. To overcome this problem, a novel technique called distal laser and proximal ligation (DLPL) was developed using a newly invented radial emitting laser probe. This study is aimed to see the outcome in terms of recurrence and incontinence of newly described technique. Materials and methods: This prospective study was conducted in a single private institute in The Dhaka city between January 2018 and July 2019. All patients with fistula in ano of cryptoglandular origin are included in this study and evaluated in outpatient department. Fistulogram done beforehand only those with recurrent fistula tract. Patients having fistula with chron’s disease, abscess cavity, side tract or malignancy were excluded from this study. A total of fifty two (52) male patients were selected. All patients were followed up and Results were evaluated. Results: The median age of the patients was 46 years (range 22-60 years), 39 patients were primary fistula, 9 patients were recurrent fistula with history of previous fistula surgery and 4 patients were bilateral anal fistula. All patients underwent DLPL (distal laser proximal ligation) operation by radial emitting Laser probe. The mean follow up was 11 months (range 6-24 months). Forty three out of 52 fistulas showed primary healing (82.6 %) without any problem of anal incontinence. Only 6 patients developed recurrent fistula (11.53%) within 3 months of Surgery. Conclusion: The use of a diode laser source and a radial emitting laser probe in addition to conventional surgery in treating different types of anal fistula for selected group of patients is a very promising new technique in sphincterpreserving anal fistula repair. J Bangladesh Coll Phys Surg 2022; 40: 153-158